ASSESSMENT OF THE POTENTIAL OF UKRAINE’S ECONOMY IN THE SPHERE OF INCLUSIVE DEVELOPMENT - Alina Yu. Zhukovska; Oleksandr V. Dluhopolskyi; Tetiana L. Zheliuk; Oleksandr V. Brechko (Academy Review)
In contemporary conditions, national economies face numerous challenges and threats, with economic and social inequality being central. These issues provoke extensive discussions on identifying effective mechanisms and tools to mitigate poverty and eliminate discrimination in all its forms. Addressing these challenges requires the practical implementation of the principles of inclusive development within the framework of national economic management. This study aims to analyze the structural components of the national economy’s potential for inclusive development, formulate a methodology for its assessment, apply this methodology to the case of Ukraine, and propose strategies for the optimal utilization of Ukraine’s existing potential in the sphere of inclusive development. The research employs systematization methods, Porter’s model, correlation-regression analysis, and normalization techniques. The findings indicate that the potential of the Ukrainian economy in the domain of inclusive development is still in its formative stage. The study reveals that the most significant contributors to the development of this potential are: production potential (GDP per capita: 0.561947), financial potential (the proportion of state budget expenditures on social protection and security: 0.07946), investment potential (gross national savings: 0.077749), digital potential (the proportion of individuals using high-speed Internet services: 0.040381), and institutional potential (perception of corruption in the public sector among business circles and experts: 0.053032). Conversely, the elements with the least impact on inclusive development include innovative potential (the proportion of GDP spent on research and development: 0.000843), labor potential (unemployment rate: 0.001797), scientific potential (number of research and development organizations: 0.002018), and human potential (literacy rate: 0.001266; average years of education: 0.00186). The study identifies several negative trends that hinder inclusive development in Ukraine. These include labor, demographic, and human potential, which are affected by high levels of migration and internally displaced persons; infrastructural potential, weakened by the destruction of infrastructure due to armed conflict; and institutional potential, characterized by pervasive corruption. Based on the assessment of Ukraine’s inclusive development potential, the following strategic directions are proposed to enhance its utilization: promoting the development of the ‘silver economy’ and digital economy; integrating inclusive approaches into the public administration system, healthcare services, and the entrepreneurial sector of the national economy. This research contributes to the theoretical and practical discourse on inclusive development by providing a robust methodological framework and strategic recommendations for enhancing national economic potential in alignment with inclusive development goals.